IbM Pembuatan Alat Permainan Edukatif (APE) Ramah Anak Bagi Guru Paud di Kota Bandung - Yayu Laila Sulastri; Aldila Rahma; Luki Luqmanul Hakim (LPPM UNINUS, 2017)
This Arts, Technology, and Science Program for Society is motivated by the number of ECE teachers who are not graduated from the specialized major, and still lack of understanding and skills in designing educational props. In addition, teachers' motivation to create the propsis also low. The purpose of this training is to form a working group of teachers who have knowledge in making creative and innovative props. Making props on this program has a hospitable concept for children, an environmentally friendly, and sourced from materials that are easily obtained from the environment. It has also low manufacturing costs, and implements the principles of 4R (Reduce, Reuse, Recycle and Replace) in everyday life, especially in teaching and learning process in school. The programwas implemented in ECE ofCinambo and ArcamanikDisctrict, Bandung. The program lasted for 8 months from March to October 2016. From this activity, all participants gain knowledge and skills in props-making to improve their quality and profesionalism as a teacher. In addition, this training program can open opportunities to develop entrepreneurial spirit to produce safe and environmentally friendly props for children with selling points.